2020
DOI: 10.1590/1413-81232020256.24002018
|View full text |Cite
|
Sign up to set email alerts
|

Saúde bucal e qualidade de vida de gestantes: a influência de fatores sociais e demográficos

Abstract: Resumo Este estudo buscou avaliar a relação entre fatores sociodemográficos e o impacto na Qualidade de Vida Relacionada à Saúde Bucal (QVRSB), em gestantes brasileiras usuárias do Sistema Único de Saúde. Trata-se de um estudo epidemiológico observacional transversal, desenvolvido com gestantes residentes em duas regiões com características sociodemográficas distintas. Foram entrevistadas 1.777 puérperas. Um questionário estruturado e previamente testado coletou as variáveis sociodemográficas e o Oral Health I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 18 publications
1
2
0
3
Order By: Relevance
“…It has been shown that being a single mother, having a lower education level, being an employed full‐time mother, and multi‐parity are significantly associated with decreased OHRQoL with respect to impacts on psychological disability, physical pain, and physical disability, respectively. These findings comport with studies investigating these associations among pregnant women 20 . Kim et al 21 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It has been shown that being a single mother, having a lower education level, being an employed full‐time mother, and multi‐parity are significantly associated with decreased OHRQoL with respect to impacts on psychological disability, physical pain, and physical disability, respectively. These findings comport with studies investigating these associations among pregnant women 20 . Kim et al 21 .…”
Section: Discussionsupporting
confidence: 84%
“…These findings comport with studies investigating these associations among pregnant women. 20 Kim et al 21 showed that single mothers experienced lower QoL compared to married mothers. Having many children was also related to decrease QoL among postpartum women due to increased workload, especially for mothers working full time, affecting the mothers' mental and physical health, quality of life, and oral hygiene behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Autores reforçam a interferência dos fatores sociodemográficos no impacto da qualidade de vida de gestantes e puérperas, ressaltando que uma melhor QV está associada a um maior desempenho físico e menor número de desconfortos sentidos ao longo da gravidez (PACHECO, 2020).…”
Section: Resultsunclassified
“…Sabe-se que os fatores sociodemográficos e econômicos podem influenciar na qualidade de vida relacionada à saúde bucal, como também estar associados à aquisição de conhecimentos de gestantes, interferindo no processo saúde-doença e na manutenção da saúde da mulher (PACHECO et al, 2020). Dessa forma, a partir da identificação do conhecimento das gestantes sobre a saúde bucal, este estudo busca reforçar a importância de identificar os fatores associados a esse conhecimento de modo a fomentar a necessidade de um acompanhamento odontológico durante o pré-natal, assim como a necessidade de subsidiar informações e propiciar autonomia às mães acerca do cuidado com sua saúde bucal e do bebê.…”
Section: Resultsunclassified